(untitled) (Fiep Bulletin - online, 2014)
Copacabana beach, in the south part of Rio de Janeiro beach, Brazil, is well-known and appreciated by people of all nationalities, ages, sex, social and cultural classes. In Copacabana you may see, besides the people that frequent it to have a good sun bath and sea, you may see people that see in this beach as an adequate space to practice sport and have pleasure As an important role of modern life, leisure, even as a personal option or as an opposition of work, by means of the sportive practice, mainly on the beaches of the south zone in Rio de Janeiro, it has been spreading a bigger attention to the studies related to the human being. The present study adds information to those that tried to mark the practice of bodies activities that are done on the Copacabana sand. It also tries to contribute with a bigger knowledge the applicability about the theory people that constructed the “ formal motive power” by Pierre Parlebas. In this sense some of the sportive modalities that are practiced along the Copacabana sand, are involved as a way of occupation of the free time and also as an exercise in free space. They were also conceived as a rational intervention and as a complex independent net of decisions.